Genome-Wide Identification and Expression Analysis of the CrRLK1L Gene Family in Yam (Dioscorea rotundata): Potential Roles in Growth and Tuber Development - Qiao, Qinghua; Li, Wenyan; Li, Changzhou; Zhou, Yiqing; Qiao, Wei; Sheng, Furui; He, Longfei (Tropical plant biology, 2025)
The Catharanthus roseus receptor-like kinase 1-like (CrRLK1L) family is pivotal for plant growth, development, and stress responses. However, comprehensive studies on CrRLK1L genes in yam ( Dioscorea rotundata ), a vital agricultural crop, remain limited. In this study, we identified and characterized 30 CrRLK1L genes in the yam genome. Phylogenetic analysis grouped these genes into eight clades, with clades I and II being species-specific to yam, which may indicate functional diversification. Structural analysis revealed significant diversity, with clade I and II genes containing numerous introns, while others had few or no introns, indicating potential roles in stress responses. Gene duplication analysis showed that tandem duplications may have contributed significantly to the expansion of the CrRLK1L gene family in yam, with most events occurring 10–80 million years ago (MYA). Expression profiling across different tissues and developmental stages revealed that several CrRLK1L genes are highly expressed in tubers, leaves, and flowers, suggesting their involvement in tuber expansion, carbohydrates accumulation, and flowering. Notably, DrCrRLK1L4 , a homolog of the well-studied FER gene in Arabidopsis , was significantly upregulated during early tuber expansion, suggests a potential involvement in tuber expansion. Additionally, DrCrRLK1L11 and DrCrRLK1L12 were implicated in later stages of tuber growth, potentially regulating carbohydrates accumulation. These findings provide valuable insights into the evolution and functional roles of CrRLK1L genes in yam, providing a basis for subsequent research on their role in tuber development and stress responses, with potential applications in the genetic improvement of economically important crops.